The Relationship between Scientific Literacy Skills and Argumentation Skills Through Discussion of Socioscientific Issues on the Virus Concept - Azizah, Nadia Nur; Herlanti, Yanti; Muliyah, Evi (FKIP - Universitas Riau, 2025)
Scientific literacy skills are important in science learning, but the scientific literacy skills of students in Indonesia are still relatively low based on the results of PISA 2022. Scientific literacy skills can be improved through the integration of socio-scientific issues in learning and scientific literacy knowledge can be measured through student argumentation. Therefore, a study was conducted to determine the relationship between scientific literacy skills and students' argumentation through discussions of socio-scientific issues on the concept of viruses. The research method used was the pre-experimental designs method using one-shot case study and correlational techniques. The total sample used was 53 students with a purposive sampling technique. Data collection in this study used tests in the form of scientific literacy questions and argumentation skills questions. The results of the study showed a relationship between scientific literacy skills and argumentation through discussions of socio-scientific issues on the concept of viruses with a significance value of 0.017 which indicates a significant relationship and a correlation coefficient of 0.327 which means the strength of the correlation is in the sufficient category. The average scientific literacy ability of students is 66.65 which is included in the moderate category and argumentation skills are at level 3.